Correlation Between Helicobacter pylori Infection and Tongue Manifestations: A Meta-analysis - Bo-Nan HOU; Yi-Di ZENG; Hao LIANG; Rui LIU; Xiao-Qing ZHOU; Lin ZHANG; Qing-Hua PENG (KeAi Communications Co., Ltd., 2018)
ABSTRACT: Objective To analyze the relationship between Helicobacter pylori (H. pylori) infection and the manifestations of the tongue.Methods Without language restrictions, we searched databases including CAJD, CBMdisc, CDFD, CMFD, PubMed, Cochrane, and EMBASE and made meta-analysis for all literature we have collected.Results Six studies with 975 patients and 50 healthy people in total were included in the analytic pool. There were significant differences in the numbers of H. pylori infections between patients with thin and thick tongue coatings (OR=2.02, 95% CI 1.32-3.07, P=0.001). In yellow tongue subgroup, there was a significant difference between patients with thick and thin coatings (OR=2.09, 95% CI 1.16-3.77, P=0.01). There was a significant difference in the prevalence of H. pylori infection between patients with yellow and white coatings (OR=2.86, 95% CI 2.10-3.90, P<0.001). The frequency of H. pylori infection was significantly increased in patients with red and purple tongues compared with those with pale red tongues (OR=3.42, 95% CI 2.40-4.88, P<0.001; OR=7.51, 95% CI 3.57-15.79, P<0.001).Conclusion Red or purple tongues and yellow tongues with thick coatings are indicators of a risk of H. pylori infection in patients with GI symptoms. Our study shows that tongue manifestations could serve as a feasible predictor of H. pylori infection in patients with GI symptoms, and determination of the exact association between tongue manifestations and H. pylori infection could enable an understanding of the objectivity of TCM. Long-term and rigorous controlled trials are needed in the future to evaluate the correlating factors. Keywords: Helicobacter pylori, Tongue manifestations, TCM, Meta-analysis, Systematic review